USE OF COMPUTED TOMOGRAPHIC PULMONARY ANGIOGRAPHY FOR THE DIAGNOSIS OF PULMONARY EMBOLISM; ARE WE OVERDOING IT? - Kalim, Shahid; Akhtar, Muhammad Shakil (Journal of Ayub Medical College Abbottabad, 2014)
Background: Computed tomographic pulmonary angiography (CTPA) is a gold standard test for the diagnosis of pulmonary embolism (PE), but is reported to be over prescribed. We performed this study to determine over prescription of CTPAs at a District General Hospital (DGH) in the United Kingdom. Our secondary aim was to establish a cause of its over-prescription. Methods: We retrospectively reviewed clinical data of all patients who underwent CTPAs during January 2011 to July 2013. Collected data included CTPA findings, clinical probability score, D-dimer results, chest x-ray (CXR) findings and patient's demographic data. A calculation of overall clinical probability (including initial and post CTPA values) and its cross analysis with D-dimer, CTPA and CXR findings was made. Results: Pulmonary embolism was positive in 5 (11.6%) cases. An Initial probability score was available in 16 (37.20%), and a D-dimer result was available in 33 (76.7%). Chest X-ray (CXR) was abnormal in 8 (18.6%). A coupling of total probability score with D-dimer results (CPPD) identified 10 (22.2%) potential over prescriptions. A further analysis of CPPD with CXR revealed a definite over prescription of 8 (18.6%), whereas it increased the number of an overall possible over prescription to 14 (32.6%). Conclusion: The CTPAs are being over prescribed and the main reasons behind it are poor utilization of probability scoring systems, D-dimer rule and lack of interpretation of alternative diagnosis on CXRs. Keywords: Pulmonary Embolism, Tomography, X-Ray Computed, Probability, fibrin fragment D, Prescriptions